(untitled) (Communications in Computational Physics, 2010)
Electrowetting has been proposed as a technique for manipulating droplets surrounded by air or oil. In this paper, we discuss the modeling and simulation of the droplet fission process between two parallel plates inside an electrowetting on dielectric (EWOD) device. Since the gap between the plates is small, we use the two-phase Hele-Shaw flow as a model. While there are several high order methods around, such as the immersed interface methods [1, 2], we decide to use two first-order methods for simplicity. A ghost-fluid (GF) method is employed to solve the governing equations and a local level set method is used to track the drop interface. For comparison purposes, the same set of two-phase Hele-Shaw equations are also solved directly using the immersed boundary (IB) method. Numerical results are consistent with experimental observations reported in the literature.